5(3b*3b-2b)=

Simple and best practice solution for 5(3b*3b-2b)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(3b*3b-2b)= equation:


Simplifying
5(3b * 3b + -2b) = 0

Reorder the terms for easier multiplication:
5(3 * 3b * b + -2b) = 0

Multiply 3 * 3
5(9b * b + -2b) = 0

Multiply b * b
5(9b2 + -2b) = 0

Reorder the terms:
5(-2b + 9b2) = 0
(-2b * 5 + 9b2 * 5) = 0
(-10b + 45b2) = 0

Solving
-10b + 45b2 = 0

Solving for variable 'b'.

Factor out the Greatest Common Factor (GCF), '5b'.
5b(-2 + 9b) = 0

Ignore the factor 5.

Subproblem 1

Set the factor 'b' equal to zero and attempt to solve: Simplifying b = 0 Solving b = 0 Move all terms containing b to the left, all other terms to the right. Simplifying b = 0

Subproblem 2

Set the factor '(-2 + 9b)' equal to zero and attempt to solve: Simplifying -2 + 9b = 0 Solving -2 + 9b = 0 Move all terms containing b to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 9b = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 9b = 0 + 2 9b = 0 + 2 Combine like terms: 0 + 2 = 2 9b = 2 Divide each side by '9'. b = 0.2222222222 Simplifying b = 0.2222222222

Solution

b = {0, 0.2222222222}

See similar equations:

| -x^3+5x^2+104x= | | a+6b=6 | | 3(4*8)+(85/3)-(6+3*4)= | | 2x+7=3x+5 | | 32a^2+52a-7=0 | | 3+5a=9+4 | | 5x^2-2x-20x-8=0 | | 2-2+7=3-2+5 | | 25y^2-1=0 | | 80-48w=48w+98 | | 12x-7=5x-49 | | 4y+-16.3=53.1 | | 2x-13=5-x | | -8+3x=-x+4 | | 3(4*8)+(85/3)= | | 2n-1=-17 | | 45+5x=9x+9 | | 16x^3-13x^2-3x=0 | | 2(3x+60)=155+-x+x | | a^2+7a-18=0 | | 3(x+5)=4(x+2) | | a^4b+a^2b^3=0 | | 3.5k+.75=-0.875 | | 5X+1-(3X-2)=42-35 | | 5x^2+6x-11=0 | | 4.5(x+1)+(2x+1)=0 | | 11b/6=b-5 | | 0.30x=12 | | 10h+1=25-2h | | 2(3c-1)-1=2c+9 | | 4x+19=26+4x | | -11x^2-11x-11=0 |

Equations solver categories